An Economic Evaluation of Tranexamic Acid to Prevent Postpartum Hemorrhage in Women With Vaginal Delivery: The Randomized Controlled TRAAP Trial. Issue 4 (December 2021) - Durand-Zaleski,; Deneux-Tharaux, C.; Seco, A.; Malki, M.; Frenkiel, J.; Sentilhes, L.
Abstract : ( BJOG . 2021;128:114–120) Prophylactic uterotonics have been the only method of postpartum hemorrhage (PPH) prevention. Tranexamic acid (TXA) is an antifibrinolytic agent that may prevent blood loss after delivery. Results from the Tranexamic Acid for Preventing Postpartum Hemorrhage Following a Vaginal Delivery (TRAAP) trial found that TXA use did not lower the rate of PPH (defined as blood loss >500 mL) but was associated with lower rates of the secondary outcome provider-assessed clinically significant PPH. These results suggested that using TXA with uterotonic may be a cost-effect way to prevent significant PPH. This study aimed to assess the increase in cost of vaginal delivery in women with PPH and investigate the effect of tranexamic acid on the cost of vaginal delivery.